Upaya Guru PKn dalam Melaksanakan Pembelajaran Berdiferensiasi Sesuai dengan Potensi Peserta Didik di SMP Pembangunan Laboratorium UNP - Izaturahmah, Izaturahmah; Ananda, Azwar; Montessori, Maria; Fatmariza, Fatmariza (Al-DYAS, 2025)
This research is motivated by the efforts made by PKn teachers in implementing differentiated learning according to the potential of students at SMP Pembangunan Laboratorium UNP. The purpose of this study is to describe the efforts of PKn teachers in implementing differentiated learning as well as the supporting and inhibiting factors of PKn teachers' efforts in implementing differentiated learning according to the potential of students. The type of qualitative research with descriptive methods. The research informants used the Purposive Sampling technique. Data collection techniques were carried out by interviews, observation and documentation. The data validity test used the source triangulation technique. The results of the study showed that the efforts of PKn teachers in implementing differentiated learning according to the potential of students were analyzing the results of cognitive and non-cognitive potential mapping, compiling teaching modules according to the characteristics of differentiated learning, implementing differentiated learning based on the characteristics of students, analyzing the weaknesses/deficiencies of differentiated learning that had been implemented. The supporting and inhibiting factors of PKn teachers' efforts in implementing differentiated learning according to the potential of students were: 1) Supporting factors. One of the PKn teachers is a driving teacher, there are supervision activities, there are CADAS activities, mapping of student needs is carried out. 2) Inhibiting factors. Limited time for teachers in compiling teaching modules according to student characteristics, teachers do not use varied learning methods and media.